Increasing self‐efficacy and knowledge in carer training: Hispanic versus Caucasian - Leisa Easom; Ke Wang; Gayle Alston (Wiley, 2020)
Abstract Aim Nurses are teachers to their patients and need to know best practices for diverse families living with dementia. Little is known about Hispanic beliefs around dementia knowledge and self‐efficacy that may have an impact on the learning situation. Design A pre‐/postresearch design was used in this intervention study with a baseline assessment of dementia knowledge and caregiver self‐efficacy and a reassessment at training completion. Methods Investigation of education training with two caregiver groups caring for persons with dementia: Caucasian and Hispanic. Convenience sample consisted of 567 Caucasians and 104 Hispanic dementia caregivers. Groups received training in their primary language accompanied by a training book (Dealing with Dementia Guide) also in the primary language. Results Dementia knowledge and caregiver self‐efficacy increased in both groups with the Hispanic group demonstrating significantly greater increase in self‐efficacy. The Caucasian group had a significantly greater increase in the dementia knowledge compared with the Hispanic group.